Potassium depletion in agricultural soils of Bangladesh and its possible impacts on mineral alteration: some empirical considerations - Hussain, MS; Khan, ZH; Hassan, MM (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Abstract not available J. Asiat. Soc. Bangladesh, Sci. 40(1): 157-161, June 2014